Low modulus Ti-rich biocompatible TiNbZrTaHf concentrated alloys with exceptional plasticity. Issue 7 (3rd July 2023) - Yang, C.; Yang, S. J.; Chen, L. Q.; Dong, H. K.; Duan, X. B.; Yu, C. Y.; Zhang, W. W.; Liu, L. H.
Abstract : This study investigates the evolutions of microstructure and performance of TiNbZrTaHf-based alloys from equiatomic high-entropy alloys to Ti-rich dilute alloys. A novel biocompatible alloy, Ti50 Nb12.5 Zr12.5 Ta12.5 Hf12.5, was developed with a high yield strength of 839 ± 12 MPa, low modulus of 61.5 GPa, low magnetic susceptibility of ∼1.99 × 10 −6 cm 3 g −1, and unprecedented tensile plasticity of 28.7 ± 2.2%. The study discusses the underlying mechanisms responsible for these superior performances, attributing the exceptional plasticity to the activation of cross-slip dislocations, enhanced dynamic recovery and high resistance to crack propagation. The findings provide new insights into the development of biomedical titanium alloys. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: This study introduces a novel biocompatible concentrated alloy with high strength, low modulus and unprecedented ductility, providing new insights for developing high-performance biomedical titanium alloys.